2022
DOI: 10.1080/08897077.2022.2060435
|View full text |Cite
|
Sign up to set email alerts
|

Familial Support in Integrated Treatment with Antiretroviral Therapy and Medications for Opioid use Disorder in Vietnam: A Qualitative Study

Abstract: Background: Patients report that familial support can facilitate initiation and maintenance of antiretroviral therapy (ART) and medications for opioid use disorder (MOUD). However, providing such support can create pressure and additional burdens for families of people with opioid use disorder (OUD) and HIV. We examined perspectives of people with HIV receiving treatment for OUD in Vietnam and their family members. Methods: Between 2015 and 2018, we conducted face-to-face qualitative interviews with 44 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Besides SMS intervention, Brown et al. (2022) demonstrated that family support facilitated ART initiation and promoted medication adherence among HIV patients. This finding was corroborated by the study by Pugh et al.…”
Section: Resultsmentioning
confidence: 99%
“…Besides SMS intervention, Brown et al. (2022) demonstrated that family support facilitated ART initiation and promoted medication adherence among HIV patients. This finding was corroborated by the study by Pugh et al.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, living with many family members, having many close friends and relatives, and having a high social support score were protective factors against opioid relapse for Vietnamese MMT patients. As a result, during MMT and in patients’ lives, family members, relatives, friends, and the community can support them to reduce stress, overcome discrimination, improve their health-related quality of life, and contribute to lowering the risk of opioid relapse [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patients who received medication instruction and HIV knowledge through SMS develop positive attitudes toward medicine and signi cantly have fewer treatment interruptions [94]. Griffee et al [99] demonstrated that family support facilitated ART initiation and promoted medication adherence among HIV patients. This nding was corroborated by the study by Pugh [98].…”
Section: Cluster 4 (Orange): Hiv Nursing Improves Medication Adherencementioning
confidence: 99%